A porous composite filler for efficiently removing total nitrogen from domestic sewage and its application
Through the coordinated design of porous zeolite and single-pore hollow-core nanocarbon ball composite filler, the problem of low efficiency of porous composite filler in the prior art in removing total nitrogen from domestic sewage is solved, and efficient and stable total nitrogen removal effect is achieved.
Patent Information
- Application Number
- CN202411931723.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing porous composite fillers are inefficient in removing total nitrogen from domestic wastewater and lack active sites for removing nitrogen under anaerobic conditions, which limits the efficiency of nitride removal.
Single-porous hollow-core nanocarbon spheres were prepared by hydrothermal and pyrolysis methods to form a high specific surface area and an oxygen-free environment to enhance the removal performance of nitrogen compounds.
It significantly improves the efficiency of total nitrogen removal in domestic wastewater, enhances the durability and chemical stability of the material, and solves the problems of high mass transfer resistance and poor adsorption performance.
Smart Images

Figure CN119368141B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sewage treatment materials, and in particular to a porous composite filler for efficiently removing total nitrogen from domestic sewage and an application thereof. Background Art
[0002] With the acceleration of urbanization and the continuous growth of population, the discharge of domestic sewage continues to rise. Among them, total nitrogen (TN) is one of the main pollutants in sewage. If it is not effectively removed, it will lead to eutrophication of water bodies, induce blue algae outbreaks, water odor and serious imbalance of the ecosystem. Therefore, in typical application scenarios such as municipal sewage treatment plants, industrial wastewater treatment systems and artificial wetlands, efficient removal of total nitrogen has become a key issue that needs to be solved urgently. In response to this demand, the performance requirements of filler materials are particularly important. First, the material needs to have a high specific surface area and excellent pore structure to provide sufficient adsorption sites to achieve efficient capture and transmission of nitrogen compounds; secondly, the material needs to maintain chemical corrosion resistance and structural stability in a complex sewage environment, and be able to operate for a long time without degradation or failure; in addition, considering that some units in sewage treatment are in an anaerobic environment, the filler needs to have the ability to provide active sites for nitrogen removal under anaerobic conditions to enhance the removal efficiency of nitrogen compounds. Meeting these performance requirements can not only significantly improve sewage treatment efficiency, reduce energy consumption and operating costs, but also achieve deep treatment of total nitrogen in sewage, promote the water treatment industry to develop in a green and sustainable direction, and provide important guarantees for global ecological environment protection and water resources management.
[0003] Although the research on porous filler materials in sewage treatment has made certain progress in recent years, there are still many limitations. For example, the invention patent with patent number CN116693061A discloses a high-efficiency porous composite filler for artificial wetlands and its preparation method. The porous composite filler can remove ammonia nitrogen, nitrogen and phosphorus in sewage, but its specific surface area is low, resulting in limited adsorption capacity of the material, which limits the removal efficiency of nitrides. In addition, under anaerobic conditions, existing porous materials usually lack special active sites for nitrogen removal and cannot effectively promote the conversion and removal of nitrides, which further limits the application ability of fillers in anaerobic treatment units. The reasons for the above problems mainly include insufficient fine control of pore structure during material preparation, inability to achieve high connectivity and stable pore size distribution, and lack of systematic optimization of functionalized surface design, resulting in less number and distribution of active sites. Therefore, it is urgent to develop a porous composite filler with high specific surface area, stable pore structure and active sites for nitrogen removal in an anaerobic environment to break through the bottleneck of existing technologies, improve sewage treatment efficiency, and meet the practical application needs of efficient removal of total nitrogen. Summary of the invention
[0004] (1) Technical issues solved
[0005] The purpose of the present invention is to provide a porous composite filler for efficiently removing total nitrogen from domestic sewage and a preparation method thereof, so as to solve the problems of low adsorption efficiency and insufficient performance of removing total nitrogen from domestic sewage of the current porous composite filler.
[0006] (2) Technical solution
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A porous composite filler for efficiently removing total nitrogen from domestic sewage, wherein the porous composite filler is a porous zeolite / nano carbon ball composite filler;
[0009] The porous zeolite / nano-carbon sphere composite filler comprises porous zeolite and single-porous hollow-core nano-carbon spheres loaded on the pore surface of the porous zeolite; the mass ratio of the porous zeolite to the single-porous hollow-core nano-carbon spheres is (95.0-98.0):(2.0-5.0).
[0010] The present invention adopts porous zeolite as a filler carrier, which is mainly used to enhance the removal performance of total nitrogen in domestic sewage and provide an ideal substrate for the formation and loading of single-porous hollow nano-carbon spheres, while the single-porous hollow nano-carbon spheres can effectively enhance the removal performance of total nitrogen in domestic sewage.
[0011] Furthermore, the preparation method of the porous zeolite / nano carbon sphere composite filler comprises the following steps:
[0012] S1. Dissolve 10-24 parts of 2,4-dihydroxybenzoic acid and 5.0-12 parts of hexamethylenetetramine in 80-120 parts of deionized water by weight, stir at room temperature, then add 15-48 parts of polyethylene glycol 4000, continue stirring, and obtain an emulsion solution; the mass ratio of the 2,4-dihydroxybenzoic acid, hexamethylenetetramine and polyethylene glycol 4000 is 1:0.5:(1.5-2.0);
[0013] S2. Place 30 to 45 parts of porous zeolite in an emulsion solution and allow to stand for immersion to obtain an emulsion solution containing porous zeolite; subject the emulsion solution containing the porous zeolite to a hydrothermal reaction, and wash and dry the obtained solid product to obtain a porous zeolite loaded with a carbon source; and then pyrolyze the porous zeolite loaded with a carbon source under an Ar atmosphere to obtain the porous zeolite / nano-carbon ball composite filler.
[0014] The single-hole hollow nano-carbon sphere of the present invention is prepared by a hydrothermal method combined with a pyrolysis method. Its unique cavity structure provides a large specific surface area and abundant active sites, and forms an internal oxygen-free environment at the same time, which is one of the core mechanisms of the present invention to achieve efficient nitrogen removal. In sewage treatment, the oxygen-free environment effectively avoids the occurrence of oxidative side reactions, strengthens the conversion and decomposition reactions of nitrogen compounds, and significantly improves the denitrification efficiency. In addition, the cavity characteristics provide a specific reaction microenvironment for nitrogen molecules and other reaction intermediates, further enhancing the selectivity and efficiency of denitrification. The carbon material has excellent chemical stability and conductivity, which not only improves the durability of the material, but also promotes the electron transfer process of nitrogen compounds through its surface activity in the denitrification mechanism, accelerating the reaction rate. The preparation process of carbon spheres uses a hydrothermal method to achieve uniform distribution and preliminary forming of the precursor, and then completes the solidification and cavity formation of carbon spheres by pyrolysis under an inert atmosphere, ensuring its chemical stability and structural integrity. In summary, single-porous hollow nanocarbon spheres show excellent performance in the removal of total nitrogen due to their internal oxygen-free environment, high specific surface area and optimized pore size distribution, providing an efficient solution for wastewater treatment.
[0015] Furthermore, the step S2 specifically includes the following steps:
[0016] S21, placing 30 to 45 parts of porous zeolite into the emulsion solution, and vacuum impregnating for 20 to 30 minutes at 200 to 400 Pa, and obtaining an emulsion solution containing porous zeolite after the impregnation is completed;
[0017] S22, placing the emulsion solution containing the porous zeolite into a Teflon-lined stainless steel autoclave for hydrothermal reaction, heating the hydrothermal reaction to 160-180°C for 200-300 min, cooling to room temperature after the reaction is completed, centrifuging at a speed of 12000-14000 rpm for 5-10 min to collect the solid product, then washing the solid product with deionized water, and drying under vacuum at 50-60°C for 240-360 min, to obtain a porous zeolite loaded with a carbon source after drying;
[0018] S23, placing the porous zeolite loaded with the carbon source into a tubular furnace for pyrolysis, the pyrolysis temperature is 600-700°C, the pyrolysis time is 120-180 min, the pyrolysis atmosphere is Ar atmosphere, and cooling to room temperature after the pyrolysis is completed to obtain the porous zeolite / nano carbon ball composite filler.
[0019] Furthermore, the preparation method of the porous zeolite comprises the following steps:
[0020] 1) In parts by weight, 20-40 parts of nano-zeolite powder, 0.3-1.0 parts of ammonium polyacrylate, 50-100 parts of deionized water, 0.5-1.2 parts of polyvinyl alcohol and 0.1-0.5 parts of polydimethylsiloxane are used to prepare a suspension by ball milling; the average particle size of the nano-zeolite powder is 200-800 nm;
[0021] 2) After the suspension is degassed, it is placed in a mold and frozen using an ice template method, then freeze-dried, and then sintered to obtain the porous zeolite.
[0022] Furthermore, step 2) includes the following steps: degassing the suspension at 20-30 kPa for 10-15 minutes; after the degassing, pouring the suspension into a polytetrafluoroethylene mold with a copper plate at the bottom, placing it in a freezing environment of -20--50°C, and after the suspension is completely solidified, freeze-drying the frozen product at -50--40°C for 8-12 hours, and then heating the freeze-dried product to 1200-1400°C at a heating rate of 5-10°C / min, keeping it warm for 120-240 minutes, and then cooling it to room temperature to obtain the porous zeolite.
[0023] The porous zeolite of the present invention is prepared by an ice template method combined with a sintering method to form a highly connected directional columnar pore structure, which not only has a high specific surface area and excellent mass transfer performance, but also provides immobilization support for the uniform distribution and stable attachment of carbon balls. In terms of nitrogen removal mechanism, the pore structure of the porous zeolite can capture ammonia nitrogen and nitrate nitrogen in water through its excellent adsorption performance, and at the same time, the acidic sites on its surface are physically adsorbed or chemically combined with nitrogen compounds, thereby achieving efficient removal of nitrogen pollutants. During the preparation process, the porous zeolite adsorbs the precursor in the emulsion solution by vacuum impregnation, fixes it on the pore surface by a hydrothermal method, and finally completes the growth and solidification of carbon balls by a pyrolysis method. The columnar pore structure of the zeolite plays a core role in guiding the distribution of precursors and supporting the generation of carbon balls, and maintains structural stability under high temperature treatment. Through a refined preparation process, the porous zeolite and the carbon balls achieve synergy, providing a solid structural foundation and functional guarantee for the efficient removal of total nitrogen in sewage, and the nitrogen removal mechanism of the porous zeolite further enhances the comprehensive performance of the material.
[0024] Furthermore, the preparation method of the nano zeolite powder comprises the following steps: adding 50 to 100 parts of zeolite raw material, 0.15 to 0.45 parts of polyethylene glycol 400, and 100 parts of anhydrous ethanol into a ball mill by weight, setting the ball mill speed to 300 to 700 rpm, and the ball milling time to 10 to 15 hours. After the ball milling is completed, a ball milling mixture is obtained, and then the ball milling mixture is filtered to obtain the treated zeolite, which is then washed with anhydrous ethanol, and finally the washed product is dried at 60 to 120° C. for 6 to 12 hours, and the nano zeolite powder is obtained after cooling.
[0025] Furthermore, the porous zeolite has a highly connected oriented columnar pore structure; the average diameter of the columnar pores of the porous zeolite is 50-200 μm.
[0026] Furthermore, the average diameter of the single-hole hollow nano-carbon spheres is 150-300 nm; the average pore size of the single-hole hollow nano-carbon spheres is 30-100 nm.
[0027] Furthermore, the specific surface area of the porous zeolite / nano carbon sphere composite filler is 300-600 m² / g.
[0028] The synergy of the two components of the porous zeolite and the single-porous hollow nano-carbon spheres in the composite filler of the present invention is manifested as a high degree of complementarity in structure and function. The porous zeolite provides an ideal distribution and fixation environment for the single-porous hollow nano-carbon spheres, and its columnar pore structure significantly reduces the mass transfer resistance during sewage treatment; the single-porous hollow nano-carbon spheres accelerate the conversion and decomposition reactions of nitrogen compounds in their internal anaerobic environment, further improving the nitrogen removal efficiency. The specific surface area of the composite filler reaches 300~600m² / g. This high specific surface area not only enhances the adsorption capacity of the composite material for nitrogen compounds, but also provides more active sites for the denitrification reaction. Overall, the combination of porous zeolite and single-porous hollow nano-carbon spheres achieves structural optimization and performance improvement from macro to micro.
[0029] In summary, the present invention successfully constructed a porous composite filler for efficiently removing total nitrogen from domestic sewage through the coordinated design of the anaerobic environment nitrogen removal mechanism of single-porous hollow nano-carbon balls and the columnar pore structure of porous zeolite. The distribution and fixation of single-porous hollow nano-carbon balls in the pores of zeolite effectively avoid the aggregation problem of carbon balls, while its cavity characteristics improve the selectivity and efficiency of the nitrogen removal reaction; the unique pore structure of porous zeolite optimizes the mass transfer path and improves the capture capacity of nitrogen compounds. The synergistic effect of the two components and the refined design of the preparation process ensure the high efficiency and stability of the composite filler in sewage treatment, providing an innovative solution for the removal of total nitrogen in domestic sewage.
[0030] The present invention also provides a porous composite filler for efficiently removing total nitrogen from domestic sewage and its application in municipal sewage treatment plants, industrial wastewater treatment and artificial wetland systems.
[0031] (3) Beneficial technical effects
[0032] 1. The present invention realizes the efficient removal of total nitrogen in domestic sewage through the innovative design of porous zeolite, which is significantly better than the existing technology. The porous zeolite is prepared by ice template method combined with sintering method to form a highly connected directional columnar pore structure, which has excellent ammonia nitrogen and nitrate nitrogen adsorption capacity and mass transfer performance, and provides a large number of acid sites, which are physically adsorbed and chemically combined with nitrogen compounds, thereby enhancing the deep removal effect of nitrogen pollutants. Its directional columnar pores not only optimize the material transfer path, but also maintain good structural stability after high temperature treatment. The high specific surface area of porous zeolite significantly improves its adsorption performance and provides an ideal substrate for subsequent loading of other functional materials. The present invention shows unique advantages in sewage treatment efficiency, material stability and environmental friendliness through a refined zeolite preparation process, and provides an efficient and reliable solution for the removal of total nitrogen in sewage.
[0033] 2. The present invention achieves efficient removal of total nitrogen in domestic sewage through the innovative design of single-hole hollow nano-carbon spheres, which is significantly better than the existing technology. Single-hole hollow nano-carbon spheres have a unique cavity structure and a high specific surface area, which can provide an internal oxygen-free environment, effectively avoid oxidation side reactions and promote the decomposition and conversion of nitrogen compounds, significantly improving the denitrification efficiency. The chemical stability and conductivity of carbon materials further enhance the electron transfer process, accelerate the reaction rate and enhance the durability of the material. The carbon spheres prepared by hydrothermal and pyrolysis methods have a uniform structure and optimized pore size distribution, which provides a specific microenvironment for nitrogen compounds and enhances the selectivity and efficiency of the reaction.
[0034] 3. The present invention constructs a porous composite filler for efficiently removing total nitrogen from domestic sewage through the coordinated design of porous zeolite and single-porous hollow nano-carbon spheres, which is significantly better than the existing technology. The columnar pore structure of porous zeolite not only optimizes the mass transfer path, but also captures nitrogen compounds through adsorption, providing a stable distribution and fixed environment for single-porous hollow nano-carbon spheres; single-porous hollow nano-carbon spheres accelerate the decomposition of nitrogen compounds by virtue of their oxygen-free cavity structure, and enhance the reaction selectivity and efficiency. The combination of the two components achieves a high degree of complementarity from structure to function. The specific surface area of the composite filler reaches 300~600m² / g, which significantly improves the adsorption capacity and the number of active sites, and effectively solves the problems of high mass transfer resistance and insufficient adsorption capacity in the existing technology. The present invention shows unique advantages in the high efficiency, stability and environmental friendliness of sewage treatment, provides an innovative solution for sewage treatment, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a macroscopic morphology of the porous composite filler prepared in Example 1 of the present invention.
[0036] Figure 2This is a SEM image of the internal structure of the porous zeolite prepared in Example 1 of the present invention.
[0037] Figure 3 This is a SEM image of the internal structure of the porous composite filler prepared in Example 1 of the present invention.
[0038] Figure 4 This is a SEM image of the internal pore surface of the porous zeolite prepared in Example 1 of the present invention.
[0039] Figure 5 This is a SEM image of single-hole hollow nano-carbon spheres on the pore surface of the porous composite filler prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0040] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0041] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.
[0042] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies
[0043]
[0044] Embodiment 1:
[0045] A porous composite filler for efficiently removing total nitrogen from domestic sewage, the porous composite filler being a porous zeolite / nano-carbon sphere composite filler; the porous zeolite / nano-carbon sphere composite filler comprising a porous zeolite and a single-porous hollow nano-carbon sphere loaded on the pore surface of the porous zeolite; the mass ratio of the porous zeolite to the single-porous hollow nano-carbon sphere is 95.0:5.0.
[0046] The preparation method of the porous zeolite / nano carbon sphere composite filler of this embodiment comprises the following steps:
[0047] S1. Dissolve 10 parts of 2,4-dihydroxybenzoic acid and 5.0 parts of hexamethylenetetramine in 80 parts of deionized water by weight, stir at room temperature, then add 15 parts of polyethylene glycol 4000, continue stirring, and obtain an emulsion solution;
[0048] S2. Put 30 parts of porous zeolite into the emulsion solution, vacuum impregnate for 20 minutes at 200Pa, and obtain an emulsion solution containing porous zeolite after the impregnation is completed; put the emulsion solution containing porous zeolite into a Teflon-lined stainless steel autoclave for hydrothermal reaction, heat the hydrothermal reaction to 160°C and keep it warm for 200 minutes, cool to room temperature after the reaction is completed, centrifuge at a speed of 12000rpm for 5 minutes to collect the solid product, then wash the solid product with deionized water, and dry it at 50°C under vacuum for 240 minutes, and obtain a porous zeolite loaded with a carbon source after drying; put the porous zeolite loaded with a carbon source into a tubular furnace for pyrolysis, the pyrolysis temperature is 600°C, the pyrolysis time is 120 minutes, and the pyrolysis atmosphere is Ar atmosphere. After the pyrolysis is completed, cool to room temperature to obtain the porous zeolite / nano-carbon ball composite filler.
[0049] The preparation method of the porous zeolite of the present embodiment specifically comprises the following steps: by weight, 20 parts of nano zeolite powder, 0.3 parts of ammonium polyacrylate, 50 parts of deionized water, 0.5 parts of polyvinyl alcohol and 0.1 parts of polydimethylsiloxane are added to a ball mill, and a uniform and stable suspension is obtained after ball milling at a speed of 250 rpm for 240 minutes, wherein the average particle size of the nano zeolite powder is 200 nm; then the suspension is degassed at 20 kPa for 10 minutes; after the degassed treatment, the suspension is poured into a polytetrafluoroethylene mold with a copper plate at the bottom, and is placed in a freezing environment of -20°C. After the suspension is completely solidified, the frozen molded product is freeze-dried at -50°C for 8 hours, and then the freeze-dried product is heated to 1200°C at a heating rate of 5°C / min, kept warm for 120 minutes, and then cooled to room temperature to obtain the porous zeolite.
[0050] The preparation method of the nano zeolite powder of the present embodiment comprises the following steps: by weight, 50 parts of zeolite raw material, 0.15 parts of polyethylene glycol 400, and 100 parts of anhydrous ethanol are added into a ball mill, the ball mill speed is set to 300 rpm, and the ball milling time is 10 hours. After the ball milling is completed, a ball milling mixture is obtained, and then the ball milling mixture is filtered to obtain the treated zeolite, which is then washed with anhydrous ethanol, and finally the washed product is dried at 60° C. for 6 hours, and the nano zeolite powder is obtained after cooling.
[0051] The porous zeolite of this embodiment has a highly connected directional columnar pore structure; the average diameter of the columnar pores of the porous zeolite is 50 μm. The average diameter of the single-porous hollow nano-carbon spheres is 150 nm; the average pore size of the single-porous hollow nano-carbon spheres is 30 nm. The specific surface area of the porous zeolite / nano-carbon sphere composite filler is 600 m² / g.
[0052] pass Figures 1 to 5 , which can prove the remarkable characteristics of the porous composite filler prepared in Example 1 of the present invention in terms of structure and morphology. Figure 1 The macroscopic morphology of the porous composite filler is demonstrated, clearly showing the porous structural characteristics. Figure 2 and Figure 3 The columnar pores inside the porous zeolite and porous composite filler are shown respectively. Figure 3 The particles attached to the columnar pores can be clearly seen, indicating that the composite filler has a good loading capacity on the pore structure. Figure 4 and Figure 5 The microscopic morphology of the pore surface of porous zeolite and porous composite filler is shown respectively. Figure 4 The pore surface of the mesoporous zeolite is relatively smooth and no single-hole hollow nanocarbon spheres are found. Figure 5 It clearly shows that there are a large number of single-hole hollow nano-carbon spheres on the pore surface of the porous composite filler.
[0053] Embodiment 2:
[0054] A porous composite filler for efficiently removing total nitrogen from domestic sewage, the porous composite filler being a porous zeolite / nano-carbon sphere composite filler; the porous zeolite / nano-carbon sphere composite filler comprising a porous zeolite and a single-porous hollow nano-carbon sphere loaded on the pore surface of the porous zeolite; the mass ratio of the porous zeolite to the single-porous hollow nano-carbon sphere is 95.9:4.1.
[0055] The preparation method of the porous zeolite / nano carbon sphere composite filler of this embodiment comprises the following steps:
[0056] S1. Dissolve 14.2 parts of 2,4-dihydroxybenzoic acid and 7.1 parts of hexamethylenetetramine in 92 parts of deionized water by weight, stir at room temperature, then add 25 parts of polyethylene glycol 4000, continue stirring, and obtain an emulsion solution;
[0057] S2. Put 34.5 parts of porous zeolite into the emulsion solution, vacuum impregnate for 23 minutes at 260Pa, and obtain an emulsion solution containing porous zeolite after impregnation; put the emulsion solution containing porous zeolite into a Teflon-lined stainless steel autoclave for hydrothermal reaction, heat the hydrothermal reaction to 166°C and keep it warm for 230 minutes, cool to room temperature after the reaction is completed, centrifuge at a speed of 12600rpm for 6.5 minutes to collect the solid product, then wash the solid product with deionized water, and dry it at 53°C under vacuum for 276 minutes, and obtain a porous zeolite loaded with a carbon source after drying; put the porous zeolite loaded with a carbon source into a tubular furnace for pyrolysis, the pyrolysis temperature is 630°C, the pyrolysis time is 138 minutes, and the pyrolysis atmosphere is Ar atmosphere. After the pyrolysis is completed, cool to room temperature to obtain the porous zeolite / nano carbon ball composite filler.
[0058] The preparation method of the porous zeolite of the present embodiment specifically comprises the following steps: by weight, 26 parts of nano zeolite powder, 0.5 parts of ammonium polyacrylate, 65 parts of deionized water, 0.7 parts of polyvinyl alcohol and 0.2 parts of polydimethylsiloxane are added to a ball mill, and a uniform and stable suspension is obtained after ball milling at a speed of 280 rpm for 258 minutes, wherein the average particle size of the nano zeolite powder is 380 nm; then the suspension is degassed at 23 kPa for 11.5 minutes; after the degassed treatment, the suspension is poured into a polytetrafluoroethylene mold with a copper plate at the bottom, and is placed in a freezing environment at -29°C. After the suspension is completely solidified, the frozen molded product is freeze-dried at -47°C for 9.2 hours, and then the freeze-dried product is heated to 1260°C at a heating rate of 6.5°C / min, kept warm for 156 minutes, and then cooled to room temperature to obtain the porous zeolite.
[0059] The preparation method of the nano zeolite powder of this embodiment comprises the following steps: adding 65 parts of zeolite raw material, 0.24 parts of polyethylene glycol 400 and 100 parts of anhydrous ethanol into a ball mill by weight, setting the ball mill speed to 420 rpm and the ball milling time to 11.5 hours. After the ball milling is completed, a ball milling mixture is obtained, and then the ball milling mixture is filtered to obtain the treated zeolite, which is then washed with anhydrous ethanol, and finally the washed product is dried at 78° C. for 7.8 hours, and the nano zeolite powder is obtained after cooling.
[0060] The porous zeolite of this embodiment has a highly connected directional columnar pore structure; the average diameter of the columnar pores of the porous zeolite is 95μm. The average diameter of the single-porous hollow nano-carbon spheres is 195nm; the average pore size of the single-porous hollow nano-carbon spheres is 51nm. The specific surface area of the porous zeolite / nano-carbon sphere composite filler is 490m² / g.
[0061] Embodiment 3:
[0062] A porous composite filler for efficiently removing total nitrogen from domestic sewage, the porous composite filler being a porous zeolite / nano-carbon sphere composite filler; the porous zeolite / nano-carbon sphere composite filler comprising a porous zeolite and a single-porous hollow nano-carbon sphere loaded on the pore surface of the porous zeolite; the mass ratio of the porous zeolite to the single-porous hollow nano-carbon sphere is 96.8:3.2.
[0063] The preparation method of the porous zeolite / nano carbon sphere composite filler of this embodiment comprises the following steps:
[0064] S1. Dissolve 18 parts of 2,4-dihydroxybenzoic acid and 9 parts of hexamethylenetetramine in 104 parts of deionized water by weight, stir at room temperature, then add 35 parts of polyethylene glycol 4000, continue stirring, and obtain an emulsion solution;
[0065] S2. Put 39 parts of porous zeolite into the emulsion solution, vacuum impregnate for 26 minutes at 320Pa, and obtain an emulsion solution containing porous zeolite after impregnation; put the emulsion solution containing porous zeolite into a Teflon-lined stainless steel autoclave for hydrothermal reaction, heat the hydrothermal reaction to 172°C and keep it warm for 260 minutes, cool to room temperature after the reaction is completed, centrifuge at a speed of 13200rpm for 8 minutes to collect the solid product, then wash the solid product with deionized water, and dry it at 56°C under vacuum for 312 minutes, and obtain a porous zeolite loaded with a carbon source after drying; put the porous zeolite loaded with a carbon source into a tubular furnace for pyrolysis, the pyrolysis temperature is 660°C, the pyrolysis time is 156 minutes, the pyrolysis atmosphere is Ar atmosphere, and cool to room temperature after the pyrolysis is completed to obtain the porous zeolite / nano-carbon ball composite filler.
[0066] The preparation method of the porous zeolite of the present embodiment specifically comprises the following steps: by weight, 32 parts of nano zeolite powder, 0.7 parts of ammonium polyacrylate, 80 parts of deionized water, 0.9 parts of polyvinyl alcohol and 0.3 parts of polydimethylsiloxane are added to a ball mill, and a uniform and stable suspension is obtained after ball milling at a speed of 310 rpm for 276 minutes, wherein the average particle size of the nano zeolite powder is 560 nm; then the suspension is degassed at 26 kPa for 13 minutes; after the degassed treatment, the suspension is poured into a polytetrafluoroethylene mold with a copper plate at the bottom, and is placed in a freezing environment at -38°C. After the suspension is completely solidified, the frozen molded product is freeze-dried at -44°C for 10.4 hours, and then the freeze-dried product is heated to 1320°C at a heating rate of 8°C / min, kept warm for 192 minutes, and then cooled to room temperature to obtain the porous zeolite.
[0067] The preparation method of the nano zeolite powder of the present embodiment comprises the following steps: by weight, 80 parts of zeolite raw material, 0.33 parts of polyethylene glycol 400, and 100 parts of anhydrous ethanol are added into a ball mill, the ball mill speed is set to 540 rpm, and the ball milling time is 13 hours. After the ball milling is completed, a ball milling mixture is obtained, and then the ball milling mixture is filtered to obtain a treated zeolite, which is then washed with anhydrous ethanol, and finally the washed product is dried at 96° C. for 9.6 hours, and the nano zeolite powder is obtained after cooling.
[0068] The porous zeolite of this embodiment has a highly connected directional columnar pore structure; the average diameter of the columnar pores of the porous zeolite is 140 μm. The average diameter of the single-porous hollow nano-carbon spheres is 240 nm; the average pore size of the single-porous hollow nano-carbon spheres is 72 nm. The specific surface area of the porous zeolite / nano-carbon sphere composite filler is 400 m² / g.
[0069] Embodiment 4:
[0070] A porous composite filler for efficiently removing total nitrogen from domestic sewage, the porous composite filler being a porous zeolite / nano-carbon sphere composite filler; the porous zeolite / nano-carbon sphere composite filler comprising a porous zeolite and a single-porous hollow nano-carbon sphere loaded on the pore surface of the porous zeolite; the mass ratio of the porous zeolite to the single-porous hollow nano-carbon sphere is 98.0:2.0.
[0071] The preparation method of the porous zeolite / nano carbon sphere composite filler of this embodiment comprises the following steps:
[0072] S1. Dissolve 24 parts of 2,4-dihydroxybenzoic acid and 12 parts of hexamethylenetetramine in 120 parts of deionized water, stir at room temperature, then continue to add 48 parts of polyethylene glycol 4000, continue to stir, and obtain an emulsion solution; the mass ratio of the 2,4-dihydroxybenzoic acid, hexamethylenetetramine and polyethylene glycol 4000 is 1:0.5:2.0;
[0073] S2. Put 45 parts of porous zeolite into the emulsion solution, vacuum impregnate for 30 minutes at 400Pa, and obtain an emulsion solution containing porous zeolite after impregnation; put the emulsion solution containing porous zeolite into a Teflon-lined stainless steel autoclave for hydrothermal reaction, heat the hydrothermal reaction to 180°C and keep it warm for 300 minutes, cool to room temperature after the reaction is completed, centrifuge at a speed of 14000rpm for 10 minutes to collect the solid product, then wash the solid product with deionized water, and dry it at 60°C under vacuum for 360 minutes, and obtain a porous zeolite loaded with a carbon source after drying; put the porous zeolite loaded with a carbon source into a tubular furnace for pyrolysis, the pyrolysis temperature is 700°C, the pyrolysis time is 180 minutes, the pyrolysis atmosphere is Ar atmosphere, and cool to room temperature after the pyrolysis is completed to obtain the porous zeolite / nano-carbon ball composite filler.
[0074] The preparation method of the porous zeolite of the present embodiment specifically comprises the following steps: by weight, 40 parts of nano zeolite powder, 1.0 part of ammonium polyacrylate, 100 parts of deionized water, 1.2 parts of polyvinyl alcohol and 0.5 parts of polydimethylsiloxane are added to a ball mill, and a uniform and stable suspension is obtained after ball milling at a speed of 350 rpm for 300 minutes, wherein the average particle size of the nano zeolite powder is 800 nm; then the suspension is degassed at 30 kPa for 15 minutes; after the degassed treatment, the suspension is poured into a polytetrafluoroethylene mold with a copper plate at the bottom, and is placed in a freezing environment of -50°C. After the suspension is completely solidified, the frozen molded product is freeze-dried at -40°C for 12 hours, and then the freeze-dried product is heated to 1400°C at a heating rate of 10°C / min, kept warm for 240 minutes, and then cooled to room temperature to obtain the porous zeolite.
[0075] The preparation method of the nano zeolite powder of the present embodiment comprises the following steps: adding 100 parts of zeolite raw material, 0.45 parts of polyethylene glycol 400 and 100 parts of anhydrous ethanol into a ball mill by weight, setting the ball mill speed to 700 rpm and the ball milling time to 15 hours. After the ball milling is completed, a ball milling mixture is obtained, and then the ball milling mixture is filtered to obtain the treated zeolite, which is then washed with anhydrous ethanol, and finally the washed product is dried at 120° C. for 12 hours, and the nano zeolite powder is obtained after cooling.
[0076] The porous zeolite of this embodiment has a highly connected directional columnar pore structure; the average diameter of the columnar pores of the porous zeolite is 200 μm. The average diameter of the single-porous hollow nano-carbon spheres is 300 nm; the average pore size of the single-porous hollow nano-carbon spheres is 100 nm. The specific surface area of the porous zeolite / nano-carbon sphere composite filler is 300 m² / g.
[0077] Comparative Example 1:
[0078] It is basically the same as Example 1, except that when preparing the porous zeolite, an equal amount of zeolite raw material is used instead of nano zeolite. Since the zeolite raw material is in micron scale, the porous zeolite prepared therefrom cannot form columnar pores.
[0079] Comparative Example 2:
[0080] It is basically the same as Example 1, except that the amount of ammonium polyacrylate used in preparing the porous zeolite is 1.5 parts, so the size of the pores formed is increased but unevenly distributed.
[0081] Comparative Example 3:
[0082] The difference from Example 1 is that the porous composite filler is porous zeolite, and the preparation method of the porous zeolite is the same as that of Example 1.
[0083] Comparative Example 4:
[0084] It is basically the same as Example 1, except that the nanocarbon balls in the porous zeolite / nanocarbon ball composite filler are closed-cell hollow nanocarbon balls, that is, the porous zeolite / nanocarbon ball composite filler includes porous zeolite and closed-cell hollow nanocarbon balls loaded on the pore surface of the porous zeolite, and its preparation method is different from the preparation method of the porous zeolite / nanocarbon ball composite filler in Example 1 in that the mass ratio of 2,4-dihydroxybenzoic acid, hexamethylenetetramine and polyethylene glycol 4000 is set to 1:0.5:3, and the corresponding weight portions of 2,4-dihydroxybenzoic acid, hexamethylenetetramine and polyethylene glycol 4000 are 10 parts, 5 parts and 30 parts, respectively.
[0085] Characterization Tests:
[0086] In order to study the performance of the porous composite filler for efficient removal of total nitrogen from domestic sewage, the black and smelly water body with low ammonia nitrogen and high nitrate nitrogen in the tributary was taken as the research object. The hydraulic retention time was set to 120min, and the water quality indicators monitored included total nitrogen , ammonia nitrogen , Nitrate nitrogen , chemical oxygen demand (COD) and total phosphorus (TP). The core material of the experiment is porous zeolite / nanocarbon ball composite filler, which is filled into the reaction column (the filling height accounts for 70% of the column). By adjusting the inlet conditions (pH range of 6.8-7.5), an aerobic group (dissolved oxygen DO is maintained at 46 mg / L), an anaerobic group (Ar gas is introduced to make the dissolved oxygen DO lower than 1 mg / L) and an aerobic + anaerobic alternating group (the two conditions are operated alternately, switching every 4 hours) are set.
[0087] The experiment was run for 48 hours, and water samples were collected at 48 hours to test water quality indicators such as total nitrogen, ammonia nitrogen, nitrate nitrogen, COD, total phosphorus, and dissolved oxygen. Data analysis includes calculation of removal rate (such as total nitrogen removal rate = [(initial TN-final TN) / initial TN]×100%). By comparing data between different groups, the enhancement effect of porous composite fillers in total nitrogen removal from sewage was explored. The expected result is that when the composite fillers are operated alternately under aerobic and anaerobic conditions, the total nitrogen removal efficiency can be significantly improved, and a large number of nitrifying bacteria and denitrifying bacteria can be enriched, providing efficient technical support for sewage treatment.
[0088] The properties of the porous composite fillers of Examples 1-4 and Comparative Examples 1-4 are summarized in Tables 2-4.
[0089] Table 2 Performance of aerobic groups of porous composite fillers of Examples 1 to 4 and Comparative Examples 1 to 4
[0090]
[0091] Table 3 Performance summary of the anaerobic group of porous composite fillers in Examples 1 to 4 and Comparative Examples 1 to 4
[0092]
[0093] Table 4 Performance summary of aerobic group + anaerobic group of porous composite fillers of Examples 1 to 4 and Comparative Examples 1 to 4
[0094]
[0095] According to the experimental conditions, the initial total nitrogen (TN) concentration fluctuates within the range of 50±3 mg / L, reflecting the concentration changes that may occur in actual experiments. The experimental results show that the total nitrogen removal rate of Example 3 is the highest (49.90-50.70%), indicating that the design of columnar pores and single-hole hollow nanocarbon spheres significantly enhances the denitrification performance; the total nitrogen removal rates of Examples 1-2 and Example 4 are slightly lower than those of Example 3, but are still significantly better than all comparative examples. In contrast, the removal rate of Comparative Example 1 is the lowest, mainly because the zeolite is micron-scale, which makes it impossible to form columnar pores and has poor mass transfer performance; although the removal rate of Comparative Example 4 has been improved (38.65-41.23%), it is still significantly lower than that of the embodiment, indicating that the closed-pore structure limits the mass transfer of pollutants and the ability of microbial attachment. Among all operating modes, the aerobic + anaerobic alternating group performed best, especially the total nitrogen removal rate of Example 3 reached 50.70%, further verifying the significant advantages of this design in denitrification performance.
[0096] In summary, the present invention constructs a porous composite filler for efficiently removing total nitrogen from domestic sewage through the coordinated design of porous zeolite and single-porous hollow nano-carbon spheres, which significantly improves the efficiency and stability of sewage treatment. The directional columnar pore structure of the porous zeolite optimizes the material transfer path and provides a large number of acidic sites, significantly enhancing the adsorption and removal capacity of nitrogen pollutants; the single-porous hollow nano-carbon spheres accelerate the decomposition and transformation of nitrogen compounds by virtue of their high specific surface area and oxygen-free cavity structure, further improving the denitrification efficiency. The two materials are highly complementary in structure and function, so that the composite filler shows unique advantages in specific surface area, number of active sites and durability, and effectively solves the problems of high mass transfer resistance and poor adsorption performance in the prior art. The present invention not only shows high efficiency and environmental friendliness in sewage treatment, but also provides an innovative solution for the deep removal of nitrogen pollutants, which has important practical application value and broad promotion prospects.
[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. A porous composite filler for efficiently removing total nitrogen from domestic sewage, characterized in that: The porous composite filler is a porous zeolite / nano carbon sphere composite filler; The porous zeolite / nano-carbon sphere composite filler comprises a porous zeolite and a single-porous hollow-core nano-carbon sphere loaded on the pore surface of the porous zeolite; the mass ratio of the porous zeolite to the single-porous hollow-core nano-carbon sphere is (95.0-98.0): (2.0-5.0); The preparation method of the porous zeolite / nano carbon sphere composite filler comprises the following steps: S1. Dissolve 10 to 24 parts of 2,4-dihydroxybenzoic acid and 5.0 to 12 parts of hexamethylenetetramine in 80 to 120 parts of deionized water by weight, stir at room temperature, then add 15 to 48 parts of polyethylene glycol 4000, continue stirring, and obtain an emulsion solution; S2. immerse 30 to 45 parts of porous zeolite in an emulsion solution to obtain an emulsion solution containing porous zeolite; subject the emulsion solution containing the porous zeolite to a hydrothermal reaction, and wash and dry the obtained solid product to obtain a porous zeolite loaded with a carbon source; and then pyrolyze the porous zeolite loaded with a carbon source under an Ar atmosphere to obtain the porous zeolite / nano-carbon ball composite filler.
2. The porous composite filler for efficiently removing total nitrogen from domestic sewage according to claim 1, characterized in that: The mass ratio of the 2,4-dihydroxybenzoic acid, hexamethylenetetramine and polyethylene glycol 4000 is 1:0.5:(1.5-2.0).
3. The porous composite filler for efficiently removing total nitrogen from domestic sewage according to claim 1, characterized in that: The step S2 specifically includes the following steps: S21, placing 30 to 45 parts of porous zeolite into the emulsion solution, and vacuum impregnating for 20 to 30 minutes at 200 to 400 Pa, and obtaining an emulsion solution containing porous zeolite after the impregnation is completed; S22, placing the emulsion solution containing the porous zeolite into a Teflon-lined stainless steel autoclave for hydrothermal reaction, heating the hydrothermal reaction to 160-180° C. for 200-300 min, cooling to room temperature after the reaction is completed, centrifuging at a speed of 12000-14000 rpm for 5-10 min to collect the solid product, then washing the solid product with deionized water, and drying it at 50-60° C. under vacuum for 240-360 min, and obtaining a porous zeolite loaded with a carbon source after drying; S23, placing the porous zeolite loaded with carbon source into a tubular furnace for pyrolysis, the pyrolysis temperature is 600-700°C, the pyrolysis time is 120-180 min, the pyrolysis atmosphere is Ar atmosphere, and cooling to room temperature after the pyrolysis is completed to obtain the porous zeolite / nano carbon ball composite filler.
4. The porous composite filler for efficiently removing total nitrogen from domestic sewage according to any one of claims 1 to 3, characterized in that: The preparation method of the porous zeolite comprises the following steps: 1) In parts by weight, 20-40 parts of nano-zeolite powder, 0.3-1.0 parts of ammonium polyacrylate, 50-100 parts of deionized water, 0.5-1.2 parts of polyvinyl alcohol and 0.1-0.5 parts of polydimethylsiloxane are used to prepare a suspension by ball milling; the average particle size of the nano-zeolite powder is 200-800 nm; 2) After the suspension is degassed, it is placed in a mold and frozen using an ice template method, then freeze-dried, and then sintered to obtain the porous zeolite.
5. The porous composite filler for efficiently removing total nitrogen from domestic sewage as claimed in claim 4, characterized in that: Step 2) includes the following steps: The suspension is degassed at 20-30 kPa for 10-15 minutes; after the degassed treatment, the suspension is poured into a polytetrafluoroethylene mold with a copper plate at the bottom, and is placed in a freezing environment of -20--50°C. After the suspension is completely solidified, the frozen molded product is freeze-dried at -50--40°C for 8-12 hours, and then the freeze-dried product is heated to 1200-1400°C at a heating rate of 5-10°C / min, kept warm for 120-240 minutes, and then cooled to room temperature to obtain the porous zeolite.
6. The porous composite filler for efficiently removing total nitrogen from domestic sewage as claimed in claim 4, characterized in that: The preparation method of the nano zeolite powder comprises the following steps: adding 50-100 parts of zeolite raw materials, 0.15-0.45 parts of polyethylene glycol 400 and 100 parts of anhydrous ethanol into a ball mill by weight, setting the ball mill speed to 300-700 rpm and the ball milling time to 10-15 hours, obtaining a ball milling mixture after the ball milling is completed, filtering the ball milling mixture to obtain a treated zeolite, washing it with anhydrous ethanol, and finally drying the washed product at 60-120° C. for 6-12 hours, and obtaining the nano zeolite powder after cooling.
7. A porous composite filler for efficiently removing total nitrogen from domestic sewage as claimed in any one of claims 1 to 3, characterized in that: The porous zeolite has a highly connected directional columnar pore structure; the average diameter of the columnar pores of the porous zeolite is 50-200 μm.
8. A porous composite filler for efficiently removing total nitrogen from domestic sewage as claimed in any one of claims 1 to 3, characterized in that: The average diameter of the single-hole hollow nano-carbon sphere is 150-300 nm; the average pore size of the single-hole hollow nano-carbon sphere is 30-100 nm.
9. A porous composite filler for efficiently removing total nitrogen from domestic sewage as claimed in any one of claims 1 to 3, characterized in that: The specific surface area of the porous zeolite / nano carbon ball composite filler is 300-600 m² / g.
10. Use of a porous composite filler for efficiently removing total nitrogen from domestic sewage as claimed in any one of claims 1 to 9 in municipal sewage treatment plants, industrial wastewater treatment, and artificial wetland systems.
Citation Information
Patent Citations
Efficient porous composite filler for constructed wetland and preparation method of efficient porous composite filler
CN116693061A
Biological packing as well as preparation method and application thereof
CN107628683A
Zeolite adsorbent / catalyst with hierarchical pore structure and construction method thereof
CN108854946A